A BRIEF PORTRAIT OF THE TEACHER’S HEALTH STATUS AND THE CONDITIONS OF WORK - Daiana Tito Azeredo da Silva, Liz; Maria de Almeida, Jaqueline; da Silva Almeida, Luciana; Crispim França Luquetti, Eliana (LINKSCIENCEPLACE, 2026)
The health of the teacher is an issue that needs attention because of the high rates of medical certificates presented daily in schools. The school environment has become increasingly stressful, which makes the mental health and the physical integrity of the teacher a matter of concern. Thus, the present research intends to present a picture of the mental/psychological and physical conditions, according to the conceptions of teachers who work in basic education. To this end, we will resort to the application of questionnaires for teachers who work in public schools located in the city of Campos dos Goytacazes-RJ, who are also students of PARFOR-UENF. As a theoretical contribution, the assumptions of Martins (2015) were used; Sampaio (2011); Gatti (2013); and data from the Ministry of Health. The results showed that the environment and the relationships that permeate the teaching and learning processes are factors that influence the professional performance of the teacher. Another issue to be highlighted is that despite the great wear and tear on their health, teachers consider themselves healthy, often not recognizing the symptoms that can lead to major problems.